2009
DOI: 10.1186/1471-230x-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis is associated with oxytocin deficiency, oesophageal dysmotility with hyperCCKemia, and autonomic neuropathy with hypergastrinemia

Abstract: BackgroundGastrointestinal (GI) dysmotility and autonomic neuropathy are common problems among diabetics with largely unknown aetiology. Many peptides are involved in the autonomic nervous system regulating the GI tract. The aim of this study was to examine if concentrations of oxytocin, cholecystokinin (CCK), gastrin and vasopressin in plasma differ between diabetics with normal function and dysfunction in GI motility.MethodsNineteen patients with symptoms from the GI tract who had been examined with gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
(72 reference statements)
0
20
0
2
Order By: Relevance
“…In our previous study, we found that esophageal dysmotility was associated with hyperCCKemia [22]. The elevated CCK levels may explain why the decrease in plasma leptin levels was less pronounced in the present group with esophageal dysmotility.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…In our previous study, we found that esophageal dysmotility was associated with hyperCCKemia [22]. The elevated CCK levels may explain why the decrease in plasma leptin levels was less pronounced in the present group with esophageal dysmotility.…”
Section: Discussionmentioning
confidence: 43%
“…On the other hand, the reduced GLP-1 concentration may be a compensatory mechanism to prevent a further decrease of the emptying rate. Such a compensatory downregulating mechanism has previously been described for oxytocin, as oxytocin attenuated gastric emptying in patients with gastroparesis [22,30]. GLP-1 administration during hyperglycemia has a markedly greater impact on the gastric emptying rate compared with GLP-1 administration during euglycemia [31].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Ohlsson ve ark. (20) tarafından yapılan diğer bir çalışmada, normal mide boşalma hızına sahip diabetes mellitus (DM) tanı-sı olan deneklerde OT salgılanmasında yemek sonrası artış olduğu gösterilirken, uzamış mide boşalma hızına sahip DM deneklerde yemek sonrası OT salgılamasında bu tip bir artış gösterilmemiştir. OT'nin sağlıklı kadınlarda kolon aktivitesini de arttırdığı gösterilmiş (21), ancak OT kronik konstipasyonlu hastalarda sindirim fonksiyonlarında iyileşmeye neden olmamıştır (22).…”
unclassified
“…Given the combined co-morbid conditions of disordered gastric motility and delayed gastric emptying (De Block et al, 2006;Stevens et al, 2008;Ejskjaer et al, 2009;Hyett et al, 2009;Parkman, 2010;Hejazi et al, 2012), approximately 30 to 50% of DM patients may suffer from a variety of symptoms such as pain, bloating, fullness, early satiety, anorexia, and vomiting (Ma et al, 2009;Szarka and Camilleri, 2010). Delayed gastric emptying among diabetics is closely related to poor glycemic control and cardiac autonomic neuropathy, as well as gastrointestinal hormone changes (Little et al, 2006;Chandrasekharan and Srinivasan, 2007;Mason, 2007;Huang et al, 2009Borg et al, 2009. The gastroduodenal motor dysfunctions underlying abnormally slow gastric emptying in diabetes include decreased antral contractions, impaired coordination between the antrum and duodenum, increased pyloric contractions and impaired proximal gastric relaxation (Stevens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%